THE RECYCLED TOYS AND GAMES PRODUCTION FOR AWARENESS OF SOLID WASTE PROBLEMS - Alves, Daiane Oliveira Vieira; Trindade, Bernardete (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The excessive production of waste is one of the major current environmental problems. In the most of Brazilian cities the destiny of waste is in inappropriate places, causing serious damage. Becomes increasingly urgent public awareness of the finite limits of natural resources , to provide reflection on the levels of consumption of resources required by our lifestyles with existing ecological conditions .This study ,had as objective to propose to students in the 4th year of school Manoel Carvalho Portella, greater knowledge about the problems caused by excessive waste on the environment and the important role of recycling plays in reversing this situation, besides informing how this issue is treated in the municipality Cachoeira do Sul, to come children closer to reality in which they live. In addition, a recycling workshop, by which it was sought to show students what is creatively possible to make from recyclable materials. Although students were aware of the general theme, the majority had no knowledge of how the question was treated in the municipality. Children have demonstrated interest and motivation in the production of toys proposed from recyclable materials Through the survey applied it was found that the objectives have been achieved because most of the class adequately answered the questions on the topic.